Self-confidence and knowledge in leadership in critical care: simulation with the "blindfolded" technique - Izabela Meneghesso; Isadora Freitas Marcatto; Beatriz Fernandes Wada; Maísa Guermandi; Fernanda Berchelli Girão (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To verify the contributions of using the "blindfolded" technique on nursing students' self-confidence and knowledge in critical patient care in simulated clinical scenarios. Method: A quasi-experimental study conducted with 25 nursing students from a Federal University in the inland of São Paulo between November and December 2021. The participants answered the "Self-confidence Scale" and the Checklist of CPR Knowledge, Skills and Attitudes, before and after the intervention. A descriptive analysis of the checklist was performed and the Wilcoxon test was used to evaluate the checklist and the "Self-confidence Scale". Results: There was a mean of 4.04 additional correct answers in the sample analyzed, based on the difference in the number of correct answers between both moments. A total of 80% of the sample showed an increase in knowledge. Conclusion: After the clinical simulation with the "blindfolded" technique, the students in leadership roles presented an increase in knowledge and self-confidence during the assistance provided in critical scenarios.